Enterprise Development in SMEs and Entrepreneurial Firms 2013
DOI: 10.4018/978-1-4666-2952-3.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Technology Orientation (TECHOR) for Small Firms

Abstract: This chapter explores the firm-level technology orientation construct and highlights the importance of a small firm’s dynamic capabilities in knowledge learning and management. Technology orientation (TECHOR) is comprised of three sets of technology-oriented activities: the allocation of technology resources, the development of technology competence, and the ability to sense and respond to technology opportunities that influence technology adoption and utilization. As firms engage in more of these activities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…Therefore, our identified perceived value constructs should be incorporated as part of future value theory development, especially when implementing AR at cultural heritage sites. Finally, the academic research to date focused mainly on the assessment of IT implementations within large firms (Lee et al, 2013); thus, the findings of this study add to the limited research on IT value in small organizations. In addition, the study explored the value concept from both internal and external stakeholders' point of view.…”
Section: Theoretical Contributions and Managerial Implicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, our identified perceived value constructs should be incorporated as part of future value theory development, especially when implementing AR at cultural heritage sites. Finally, the academic research to date focused mainly on the assessment of IT implementations within large firms (Lee et al, 2013); thus, the findings of this study add to the limited research on IT value in small organizations. In addition, the study explored the value concept from both internal and external stakeholders' point of view.…”
Section: Theoretical Contributions and Managerial Implicationsmentioning
confidence: 94%
“…Particularly small cultural heritage organizations have to ensure that the benefits expected by stakeholders are delivered when implementing AR, due to the high costs involved (Chesher and Skok, 2000). Furthermore, Lee et al (2013) revealed that the majority of research concerning technological developments to date focused solely on customer orientation and market orientation in large companies. Therefore, the present study uses the case study of a small museum in the UK to examine the perceived value of AR applications within the museum context using a stakeholder approach.…”
Section: Introductionmentioning
confidence: 99%
“…It is “the ability and the will to acquire a substantial technological background and use it in the development of new products” (Gatignon and Xuereb, 1997, p. 78). In the current investigation, a technology-oriented healthcare SC entity is considered as the one that is dedicated to adopt newer and emerging technologies for exchanging real-time information with its SC partners so as to improve coordination and provide enhanced healthcare services to its patients (Slater et al , 2007; Zhou et al , 2005; Lee et al , 2013; Ho et al , 2016).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Extant studies suggest discovery, variation and innovation to have an effective influence on technology-oriented organizations (Lee et al , 2013). So, firms must focus on optimizing these processes (Ho et al , 2016).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation